PERANAN INHIBITOR KATEPSIN DARI IKAN PATIN (Pangasius hypophthalmus) UNTUK MENGHAMBAT KEMUNDURAN MUTU IKAN BANDENG (Chanos chanos Forskal) - Tati Nurhayati; Ella Salamah; Komariah Tampubolon; Ary Apriland (Jurnal Pengolahan Hasil Perikanan Indonesia, 2011)
The process of deterioration of fresh  sh quality begins with an enzimatis damage, one of them is katepsin.To prevent deterioration of  sh, an inhibitor can be obtained naturally from the body of  sh. The purpose of this research was to use extract of cathepsin inhibitor from cat sh for inhibit deterioration of milk sh. This researchshowed that temperature of 80 ºC was the optimum temperature for extracting inhibitor complex with inhibitoryactivity of 92,88%. Cathepsin inhibitor gave the most effective to prevent deterioration (85,29% inhibitory activity) after diluted two fold on buffer solution. Soaking with inhibitors from cat sh katepsin capable to inhibit thedeterioration of  sh quality longer than 72 hours (3 days) compared with control  sh, milk sh (soaking in buffer).Keywords : catsh, cathepsin, inhibitor, milksh